Quality of life in patients with advanced cancer according to place of care in a referral hospital. - Amado Tineo, Jose (2021)
The quality of life perceived by patients with advanced cancer from a tertiary hospital is compared according to home care versus hospital care. Observational, cross-sectional study, included patients older than 18 years with cancer with multiple metastases. EORTC QLQ-C15-PAL quality of life survey was applied to patients with adequate cognitive level (Pfeiffer questionnaire). Chi square and Mann-Whitney, p <0.05, and SPSS 24.0 were used. 83 patients in the hospital group and 69 at home. Median age 66 and 76 years respectively (p <0.01); the female sex predominated (p = 0.60). They presented moderate or severe cognitive impairment, 25% hospital group and 58% home (p <0.01). The median quality of life score was 49.5 in the hospital group and 48 in the home group (p = 0.60), the physical functional aspect had a lower score in the hospital group (p <0.01). The perceived quality of life is acceptable, the home group is older and has cognitive impairment.